Pemaknaan Semboyan Balayar Satujuan Batambat Setangkahan dalam Mempersatukan Agama, Adat dan Budaya di Kecamatan Datuk Bandar Kota Tanjung Balai - Ramadhan, Syahri; Harahap, Elly Warnisyah; Is, Fadillah (Lembaga Yasin AlSys, 2023)
Indonesia has diversity, race, ethnicity, culture, customs, religion and several regions in this country have local beliefs. Many of the general public do not know that in every region there were beliefs held by people in ancient times. At this time there are still many who do not know very well about the contents of the values that exist in local beliefs and as a result there are still many who act intolerantly towards this original archipelago belief. The diversity of religions in Indonesia can be seen from the recognition of the five religions professed by the people in the country, namely Christianity, Islam, Hinduism, Buddhism and Confucianism. Factors that influence the diversity of Indonesian society, both from within and outside the community itself. This diversity is a challenge that can pose a threat to the integrity of the Indonesian nation. However, the existence of a motto that is formed as a reference or as a symbol of one area is able to help and reduce divisions between religious communities in that region. After conducting research, this research focuses on, 1) Having a motto/motto in one area can encourage the growth of tolerance towards differences in race, ethnicity, ethnicity, and religion. 2) Can strengthen unity in a pluralistic society. 3) It has its own meaning and meaning for each region. This research method uses a type of qualitative research. Data Collection Techniques using Interview Methods or interviews, observation, and documentation. Miles and Huberman's qualitative data analysis technique.